Microcystic, elongated, and fragmented pattern of invasion in relation to histopathologic and clinical prognostic factors in endometrioid endometrial adenocarcinoma - Naki, M. Murat; Oran, Gulbin; Tetikkurt, Seza Umit; Sonmez, Cavide Fatma; Turkmen, Ilknur; Kose, Faruk (GALENOS YAYINCILIK, 2017)
Objective: To investigate the association of microcystic, elongated, and fragmented (MELF) pattern of invasion with prognostic factors in endometrioid endometrial adenocarcinoma (EEA). Material and Methods: Stained tissue sections from 83 cases of EEA operated by the same gynecologic oncologist were reviewed to identify cases showing MELF-type invasion in this retrospective study. The association of MELF pattern with age, tumor grade, depth of myometrial invasion, and presence of lymphovascular space invasion (LVSI) was analyzed. Results: FIGO grade 2 and grade 1 tumors were evident in 53.0\% and 38.6\% of patients, respectively. Depth of myometrial invasion was <50\% in 72.0\% of patients, and LVSI was absent in 77.1\%. MELF pattern was confirmed in 35 (42.2\%) patients. Presence of MELF pattern was associated with significantly higher mean +/- standard deviation age (62.9 +/- 6.9) years vs. 58.9 +/- 9.1 years, p=0.033), and found to be more likely in patients with high-grade tumor (FIGO grade III

85.7\% vs. 14.3\%, p<0.001), deep (>= 50\%) myometrial invasion (78.3\% vs. 21.7\%, p<0.001), and presence of LVSI (94.7\% vs. 5.3\%, p<0.001) as compared with absence of MELF pattern. Conclusion: In conclusion, our findings revealed a high rate of MELF pattern among patients with EEA alongside the association of MELF pattern with poor prognostic factors such as high grade tumor, deep myometrial invasion, and LVSI.
Keywords: Endometrioid endometrial adenocarcinoma; microcystic; elongated; fragmented pattern; tumor grade; myometrial invasion; lymphovascular space invasion